The Effect of Physical Activity and Gender on Self-Esteem of Shiraz University Students - Robabeh Rostami; Hossein Mohamad- Sadeghi Poor; Mohammad Javadmanesh (Islamic Azad University, 2016)
Introduction: Many studies have shown that social interactions resulting from participation in physical activities lead to an optimal state of self-esteem. The findings of previous research on gender differences regarding this factor, however, have not been consistent. In an attempt to fill this gap, this study is designed to investigate the effect of physical activity and gender on students' self-esteem in Shiraz University. Methods: Random-Comparative method was employed to conduct this research. Population included all undergraduate students of Shiraz University. Participants were selected through random cluster sampling. 332 students filled out a Cooper Smith and Colleague's Questionnaire and the scores of 218 of them were analyzed. Two-way analysis of variance was administered for the analysis (P≤0.05). Results: The results conveyed that the major impact of gender (P=0.05) and physical activity (P=0.02) on self-esteem were both significant. Active students had higher self-esteem compared to inactive ones (P=0.02) and the self-esteem scores of female students were higher than male students (P=0.05). Conclusion: The results of this research indicate that participation in physical activities may improve the self- esteem of bachelor students studying in Shiraz University. Furthermore, the analysis of the results showed that female students enjoyed higher self- esteem.